The Palgrave Handbook of EU-Latin American Relations
XXXVI, 645 p. 31 illus., 30 illus. in color.
Keywords: "An indispensable, well documented and in-depth analysis of UE-Latin American relations as seen by renowned experts and policymakers on both sides of the Atlantic." --Luis Guillermo Solis Rivera, Former President of Costa Rica "This comprehensive Handbook offers a rigorous and updated analysis of the EU-Latin America relationship, addressing key challenges and opportunities. An indispensable reference for stakeholders interested in strengthening this strategic bi-regional partnership¨ --Antonia Urrejola, Former Minister of Foreign Affairs of Chile “Latin America and the EU have significantly contributed to peace, democracy, and global development through mutual relations and cooperation. This handbook provides fresh, informed analysis, making it an essential resource for study and constructive policy-making.” --Rebeca Grynspan, Secretary General of UNCTAD This Handbook explores the interactions within the Euro-Latin American region and analyzes the interests, norms, and practices of actors influencing the governance of interregional issues and policies. The chapters examine how states and non-state players in the Atlantic region tackle issues related to asymmetries, development disparities, and adaptation to the global system. Eight sections cover the unique characteristics of the interregional connections between the European Union (EU) and Latin America. The first examines multiple perspectives on defining and understanding Euro-Latin American Space, and the second continues with explaining the role of three leading EU institutions in the relationship with Latin America. EU relations with Latin American regions and some individual countries are the subject of sections three and four. The economic and political bi-regional agendas are explored in sections five and six. This Handbook closes with two sections focused on the societal experiences and the role of external actors. José Antonio Sanahuja is Professor of International Relations at the Complutense University of Madrid, Spain. He was the director of the Carolina Foundation and special advisor for Latin America and the Caribbean to Josep Borrell, the High Representative for Foreign Affairs and Security Policy and Vice President of the European Commission (ad honorem). Roberto Dominguez is Professor of International Relations at Suffolk University in Boston, Massachusetts, USA. He was a Jean Monnet fellow at the European University Institute in Florence and a Visiting Scholar at the Center for European Studies at Harvard University.